EVALUASI SISTEM PENGENDALIAN INTERNAL PADA SIKLUS PENJUALAN DAN PENERIMAAN KAS BUMDES XYZ PELALAWAN RIAU - Fitriyeni Oktavia (Ensiklopedia of Journal, 2023)
Sales is the agency's main business activity to earn profits and maintain business development. In an effort to optimize profits, an internal control system is needed that prevents, detects and corrects errors and fraud that can hinder the achievement of sales objectives. BUMDes XYZ is a Village-Owned Enterprise which has three business units, namely sales of building materials, fuel and BRIlink service units. The study was conducted to evaluate the internal control system in the sales and cash receipts cycle of BUMDes XYZ Pelalawan Regency, Riau. A qualitative approach with descriptive analysis is used based on data collection through interviews, observation and collection of literature studies. The data is processed by describing the description of the research object and evaluated using a theoretical study based on the components of the COSO (Committee of Sponsoring Organizations of the Treadway Commission) internal control conceptual framework. The results of this study are that it is still found that implementation is not optimal in the basic principles of internal control in the sales and cash receipts cycle which causes a lot of uncollectible receivables and sales losses.